Jewish Minority & Their Political، Economical And Cultural Roles in Iraq From 1921-1952 - AMEEN, FAKHRIA ALI (Al-Adab Journal, 2020)
The Jewish community in Iraq was one of the most largest Arab Jewish community and the oldest one . Their number estimated nearly ( 150 ) thousand people . Most of them were distributed in the biggest cities like Baghdad, Mosul, Erbil, Basrah and othersSome of Jewish families in Baghdad were the richest Jews in the world as exchangers and international traders . Iraqi Jews lived in time of Ottoman control on Iraq . And they took chance like all other denominations and religions to contribute in the nationalism movement . They cooperated their brothers Arabs side by side to serve Iraq . Like construction schools, to practice transactions, banking businesses and other activitiesThere were representatives, parliament members from them in Iraqi parliament . Many of Jews have taken up significant positions at ministries of Iraqi state during period of royal reign in Iraq . The economic retraction conditions of Iraqi Jews after independence were not hindrance against their joining within the national movementThe Iraqi constitution did not margin or forget rights of this significant sect of the Iraqi people, where first constitution of the Iraqi government in 1925, stated principle of complete rights of citizenship . As sixth article of constitution stated that various sects have the right to establish schools to teach their sons of generations with their own and mother tongue language to be conditioned in harmony with public textbooks in Iraq . And the Jews had members in the Iraqi parliament in 1946 who were six parliamentary in equal with Christian sect, but their representation was canceled after collective migration to Palestine .